The Brazilian Neurology centenary (1912-2012) and the common origin of the fields of Neurology and Psychiatry O centenário da Neurologia brasileira (1912-2012) e a origem comum das áreas de Neurologia e Psiquiatria - Marleide da Mota Gomes; Jose Luiz de Sá Cavalcanti (Arquivos de Neuro-Psiquiatria)
It is reported the Brazilian Neurology birth (1912), that has as the hallmark its first Neurology Cathedra of Rio de Janeiro, and the links between Neurology and Psychiatry, besides the main medical protagonists at that time in Rio de Janeiro: João Carlos Teixeira Brandão (1854-1921), first professor of the cathedra of Clinical Psychiatry and Nervous Diseases (1883-1921); Juliano Moreira (1873-1933), the founder of the Brazilian scientific Psychiatry and director of the Hospício Nacional de Alienados (National Hospice for the Insane) (1903-1930); Antônio Austregésilo Rodrigues de Lima (1876-1960), first professor of the cathedra of Neurology, considered the father of the Brazilian Neurology. Aloysio de Castro (1881-1959) was a great Brazilian neurosemiologist at that time. Austregésilo practiced both disciplines, Neurology and Psychiatry, and like Jean-Martin-Charcot, he was very interested in a typically psychiatric disorder, the hysteria. It is also considered in this paper the first Brazilian authors of Neurology and/or Psychiatric texts and the places where Neurology was initially developed by the main founders: Hospício Nacional de Alienados, Santa Casa de Misericórdia do Rio de Janeiro and Policlínica Geral do Rio de Janeiro. É relatado o nascimento da Neurologia brasileira (1912), que tem como marco principal a primeira Cátedra de Neurologia do Rio de Janeiro, bem como as ligações entre Neurologia e Psiquiatria, além dos principais protagonistas médicos da época naquela cidade: João Carlos Teixeira Brandão (1854-1921), primeiro professor da cátedra da Clínica psiquiátrica e de moléstias nervosas (1883-1921); Juliano Moreira (1873-1933), fundador da Psiquiatria científica brasileira e diretor do Hospício Nacional dos Alienados (1903-1930); Antônio Austregésilo Rodrigues de Lima (1876-1960), primeiro catedrático de Neurologia, considerado o pai da Neurologia brasileira. Aloysio de Castro (1881-1959) foi um grande neurosemiologista brasileiro da época. Austregésilo praticava tanto a Neurologia quanto a Psiquiatria e, como Jean Martin-Charcot, estava muito interessado em um típico transtorno psiquiátrico, a histeria. Consideram-se também os primeiros autores brasileiros de textos de Neurologia e/ou Psiquiatria e os locais onde a Neurologia foi inicialmente desenvolvida pelos fundadores principais: Hospício Nacional dos Alienados, Santa Casa de Misericórdia do Rio de Janeiro e Policlínica Geral do Rio de Janeiro.